ОНА ТИЛИ ТАЪЛИМ МАЗМУНИ ОРҚАЛИ ЛИНГВИСТИК КОМПЕТЕНЦИЯ ШАКЛЛАНТИРИШ - Тажбенова, С.С. (SCIENCE and SOCIETY, 2023)
This article describes the ways of forming linguistic competence to the content and methods of teaching the native language in elementary school.
Keywords: linguistic competence; approach; knowledge; problem; idea; theoretical knowledge; subject